Neglected cardiomyopathies in Africa - Mocumbi, Ana Olga H. (SA Heart Journal, 2017)
Cardiomyopathies are forms of disease in which the heart muscle is structurally and functionally abnormal in the absence of coronary artery disease, hypertension, valve disease and congenital heart disease sufficient to explain the observed myocardial abnormality. They constitute the greatest challenge of all the cardiovascular diseases in Africa, due to the difficulties in diagnosing and managing them, related to the lack of access to specialised investigations or effective interventions in most endemic areas. In this continent, in addition to the “usual” forms of cardiomyopathy, there is an increased incidence of specific forms of muscle heart disease like Endomyocardial Fibrosis and Peripartum Cardiomyopathy which, despite affecting thousands of people, have been largely neglected. Their etiology remains unknown, the mechanisms involved are not fully understood, and although some improvement in management has been witnessed in recent years much still need to be done to improve the outcome. The current knowledge on epidemiology, determinants, pathophysiology, diagnosis and management of Endomyocardial Fibrosis and Peripartum Cardiomyopathy is reviewed in this article, which also presents the ongoing efforts for better understanding of their pathogenesis and the recent improvements in their management.